2011
DOI: 10.1111/j.1600-048x.2011.05320.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in spring migration routes and breeding distribution of northern pintails Anas acuta that winter in Japan

Abstract: In North America, spring migration routes and breeding distribution of northern pintails Anas acuta vary because some individuals opportunistically nest at mid‐latitudes in years when ephemeral prairie wetlands are available, whereas others regularly nest in arctic and sub‐arctic regions where wetland abundance is more constant. Less was known about migration routes and breeding distribution of pintails in East Asia. From 2007–2009 we marked 198 pintails on their wintering areas in Japan with satellite transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…After reaching an initial summer site where they remained at least 27 days, some pintails moved to more northern locations, possibly to molt remiges (Hupp et al 2011). Thus, on average, pintails with PTTs were farther from Japan at the start of autumn migration than they were at the end of spring migration in early June.…”
Section: Detection Dates Of Ptts and Ringed Pintails At Common Locationsmentioning
confidence: 96%
See 4 more Smart Citations
“…After reaching an initial summer site where they remained at least 27 days, some pintails moved to more northern locations, possibly to molt remiges (Hupp et al 2011). Thus, on average, pintails with PTTs were farther from Japan at the start of autumn migration than they were at the end of spring migration in early June.…”
Section: Detection Dates Of Ptts and Ringed Pintails At Common Locationsmentioning
confidence: 96%
“…We expected that if PTTs adversely affected some aspect of migration energetics, such as the cost of flight or the accumulation and expenditure of reserves, radiomarked birds might increasingly lag behind ring recoveries as migration progressed, resulting in a positive effect of migration distance on the disparity. Hupp et al (2011) observed that migration routes of male pintails marked with PTTs differed slightly from radiomarked females, and suggested that because of skewed sex ratios, migration strategies of unpaired males might differ from paired males and females. Therefore, we considered sex of marked birds as predictor variables if genders of the radiomarked and ringed pintails differed.…”
Section: Detection Dates Of Ptts and Ringed Pintails At Common Locationsmentioning
confidence: 96%
See 3 more Smart Citations